Solubility of carbon dioxide in an aqueous blend of diethanolamine and piperazine - Mondal M.K. (My University, 2025)
The solubility of CO2 in aqueous blends of diethanolamine (DEA) and piperazine (PZ), from mixtures of CO2 and N2, was measured for temperatures and CO2 partial pressures ranging from (303.14 to 353.14) K and (10.133 to 20.265) kPa, respectively. Measurements were made by a saturation method using a laboratory scale bubble column. The results of CO 2 solubility in liquid are expressed as RCO2 (mol CO 2/mol amine) for all experimental runs. A solubility model is developed to correlate and predict the solubility data of CO2 in aqueous blends of DEA and PZ. There is an acceptable degree of agreement between the experimental data of the present study and predictions of the solubility model with an average absolute deviation of less than 4.5 %.©2009 American Chemical Society.